Synacthen Stimulation Test Following Unilateral Adrenalectomy Needs to Be Interpreted With Caution - Zaman, Shamaila; Almazrouei, Raya; Sam, Amir H.; DiMarco, Aimee N.; Todd, Jeannie F.; Palazzo, Fausto F.; Tan, Tricia; Dhillo, Waljit S.; Meeran, Karim; Wernig, Florian (Frontiers in Endocrinology, 2021)
Background. Cortisol levels in response to stress are highly variable. Baseline and stimulated cortisol levels are commonly used to determine adrenal function following unilateral adrenalectomy. We report the results of synacthen stimulation testing following unilateral adrenalectomy in a tertiary referral center. Methods. Data were collected retrospectively for 36 patients who underwent synacthen stimulation testing one day post unilateral adrenalectomy. None of the patients had clinical signs of hypercortisolism preoperatively. No patient received pre- or intraoperative steroids. Patients with overt Cushing’s syndrome were excluded. Results. The median age was 58 (31-79) years. Preoperatively, 16 (44%) patients had a diagnosis of pheochromocytoma, 12 (33%) patients had primary aldosteronism and 8 (22%) patients had non-functioning adenomas with indeterminate/atypical imaging characteristics necessitating surgery. Preoperative overnight dexamethasone suppression test results revealed that 6 of 29 patients failed to suppress cortisol to <50 nmol/L. Twenty (56%) patients achieved a stimulated cortisol ≥450 nmol/L at 30 minutes and 28 (78%) at 60 minutes. None of the patients developed clinical adrenal insufficiency necessitating steroid replacement. Conclusions. Synacthen stimulation testing following unilateral adrenalectomy using standard stimulated cortisol cut-off values would wrongly label many patients adrenally insufficient and may lead to inappropriate prescriptions of steroids to patients who do not need them.